Tinjauan Sistem Jual Beli Kredit Perabotan Rumah Tangga dalam Perspektif Ekonomi Islam di Kabupaten Kerinci - Sarmigi, Elex; Okataria, Welan; Bustami, Bustami; Nasution, Syamsarina; Harahap, Samsul Bahry (Institut Agama Islam Negeri Parepare, 2025)
This research was conducted to find out the credit system that is allowed and prohibited in Islamic economics, the practice of buying and selling household furniture goods with a credit system carried out by the people of Kerinci Regency. This research is descriptive qualitative research. There were 9 people who became informants of credit providers and creditors. The data obtained were analyzed descriptively qualitatively processed in three stages, namely data reduction, data presentation, data verification. This research found that the practice of buying and selling household furniture credit in Kerinci Regency is not in accordance with sharia principles. Although it provides convenience for the community, this system contains elements of usury through late fees, non-transparent profit margins, and a lack of understanding of sharia contracts. Low financial literacy also worsens the condition, so this practice does not fulfill the principle of maslahah in Islamic economics.